Effect of machining and drag finishing on the surface integrity and mechanical properties of Inconel 718 alloys fabricated by laser powder bed fusion additive manufacturingEinfluss der maschinellen Bearbeitung und des Schleppfinishs auf die Oberflachenintegritat und die mechanischen Eigenschaften von additiv gefertigten NiCr19NbMo-Legierungen durch Laserstrahl-Pulverbett-Schmelzen - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2022)
Laser powder bed fusion process is one of the most widely used Additive Manufacturing techniques for fabricating metal components, however the surface quality of such components still remains a challenge and fails to meet the user expectations. Thus, this study presents a systematic investigation on the effect of post-processing operations including finish milling and drag finishing on the surface integrity and resulting mechanical properties of Inconel 718 specimens fabricated by laser powder bed fusion additive manufacturing technique. The influence of post-processing operations on the surface and subsurface microstructure, microhardness and tensile strength on the Inconel 718 specimens are carefully examined and presented in this study. Finally, this work also contributes to understanding the critical wall (part) thickness that is notably induced from the post-processing operations. It is revealed that the surface integrity and resulting mechanical properties of specimens significantly improved as compared to as-built specimens once milling and drag finishing post-processing are deployed. However, the degree of impact depends on the thickness of parts subjected to post-processing.
Keywords: Surface integrity; laser powder bed fusion; additive manufacturing; post-processing operations; Inconel 718; POST-PROCESSING OPERATIONS; CORROSION BEHAVIOR; MICROSTRUCTURE